(untitled) (University of Thi-Qar Journal for Engineering Sciences, 2012)
This paper gives an experimental study for the thermal conductivity of mortar concrete material by adding polystyrene (styropr) as granules for different volume percentages (0%,5% , 10% and 15 %). Polystyrene considered as a polymeric thermal isolative material. The specimens of 343 cm3 are made with a mixing percentages of 22.72% cement, 68.18% sand and 9.1% water which they accredited according to the Iraqi standardization No. (5 /1984).Tests are carried out in the laboratories of the engineering college– Karbalaa university to determine the thermal conductivity, compressive strength, porosity and the density for the specimens. The results showed that the polystyrene leads to decrease the thermal conductivity of the mortar concrete. The thermal conductivity of the (5%) polystyrene specimen is decreased by (2.6%), (10%) polystyrene specimen is decreased by (10.4%), and for the specimen of (15%) polystyrene is decreased by (20.28%).The compressive strength of the specimen is decreased by increasing the polystyrene percentages and this clearly appear in the 10% and the 15% specimens but it isn’t exceed the permissible range according to the Iraqi standardization No. 5/1984 (compressive strength≥23 Mpa).